Exposer le patrimoine des écoles d’art en Europe : un intérêt résolument contemporain - Morwena Joly-Parvex (In Situ)
Today, the art schools of the big European capitals, which were created throughout all Europe from the 17th to the 18th century, are all asking the same questions: how can we better know, and better highlight, the heritage of art schools, and to what end? From the opening of a new museum space in the Royal Academy in London in 2016 to the opening of the Dresden school’s anatomy collection in 2018, we are compelled to admit that there is interest all across Europe in these atypical (for the museum world) collections, where known masterpieces are set next to the pedadogical drawings and plaster casts.To display these collections is to display the history of artist teaching, the way that “becoming an artist” is taught, sometimes with contradictory injunctions and varied approaches. The responses brought by the great European academies are different from each other due to their histories, they were a part of, then separated from the museum institution, and sometimes from the archaeological section of the university. By travelling across Europe, from London to the big German cities, from Madrid to Vienna and even as far as Saint Petersburg, this article aims to show a panorama of the museographic choices that were made to highlight the patrimony of art schools. The collections, which were briefly referred to as “pedagogical”, are a testimony of the history of how Italian models, and then greco-roman art, or the tenacity of the naturalist model, were seen. Thus it reveals the history of the artist’s way of seeing as shown by the choices made by the Royal Academy of London.